REACTUALIZATION OF ISLAMIC EDUCATIONAL VALUES IN THE TRANSFORMATION OF THE LEARNING CLIMATE IN THE DIGITAL ERA - Rohaedah Rohaedah; Devi Sulaeman; Mia Audina Musyadad; Irena Laras; Asep Supriatna (Indonesian Journal of Islamic Studies (IJIS), 2026)
The digital transformation in education presents both challenges and opportunities for Islamic educational institutions in maintaining their value orientation amidst changes in media and learning interaction patterns. These changes require efforts to reactualize Islamic educational values to remain relevant and operational in creating an effective and character-based learning climate. This study aims to analyze the process of reactualization of Islamic educational values in the transformation of the learning climate in the digital era at Madrasah Ibidaiyah Al Umm. The study used a qualitative approach with a case study. Data collection techniques included participant observation, in-depth interviews, and documentation studies. Data were then analyzed interactively through data reduction, data presentation, and conclusion drawing. The results indicate that value reactualization occurs through three main patterns: the integration of values into digital learning planning, the establishment of an etiquette-based classroom culture in online interactions, and teacher role models in digital communication ethics. Technological transformation is interpreted as a medium for strengthening character, not simply an innovation in learning tools. The resulting learning climate demonstrates consistency between madrasah policies, pedagogical practices, and classroom culture. The implications of this research emphasize the importance of values-based digital learning design as a foundation for character building in madrasahs, while also providing a conceptual contribution to the development of contextual Islamic education in the digital era.